PENINGKATAN KUALITAS PEMBELAJARAN IPA PADA MATERI SISTEM PENCERNAAN MANUSIA DENGAN STRATEGI JIGSAW-LESSON STUDY PADA SISWA KELAS VIII-A SMP NEGERI 3 PACITAN - Winarno, Edi (Jurnal Florea, 2014)
This study aims to improve the quality of science learning outcomes matter of human digestive systemin class VIII-A of SMP Negeri 3 Pacitan school year 2011/2012 through the implementation oflearning strategy Jigsaw - Lesson study. The results show that the quality of the science learningprocess increases . It can be seen from the increase in the percentage of success of the action on thefirst cycle of 62.59 % increased by 7.41% after the second cycle , which becomes 80.00 % and basedon the level of success include the category very well . In addition it also increases the percentage ofmastery learning in the time before the actions of 38.89 % , after the first cycle of 72.22 % and thesecond cycle in the classical mastery learning students reach 100 % . The average value of learningoutcomes also increased , at the time before the action was 71.00 , after the first cycle of 72.31 and thesecond cycle in the classical mastery learning students achieve 76.31 . From the results of this studyconcluded that learning with LS - Jigsaw strategy can improve the quality of science teaching , thestudents of class VIII - A of SMP Negeri 3 Pacitan school year 2011/2012 .Keyword: learning, jigsaw, lesson study